Comparison of sirolimus eluting stent with bioresorbable polymer to everolimus eluting stent with permanent polymer in bifurcation lesions: Results from CENTURY II trial. Issue 6 (13th August 2015) - Orvin, K; Carrie, D.; Richardt, G.; Desmet, W.; Assali, A.; Werner, G.; Ikari, Y.; Fujii, K.; Goicolea, J.; Dangoisse, V.; Manari, A.; Saito, S.; et al.
Abstract : Objective: To demonstrate the safety and efficacy of a new sirolimus eluting stent with bioresorbable polymer, Ultimaster, (BP‐SES) compared with everolimus‐eluting, permanent polymer, Xience stent (PP‐EES) in bifurcation lesions with respect to the freedom from Target Lesion Failure at 1‐year. Methods: Within 1, 119 patients enrolled in the CENTURY II randomized controlled multicenter trial, 194 patients were treated for bifurcation lesions and randomized to either BP‐SES ( n  = 95) or PP‐EES ( n  = 99). The primary endpoint was freedom from target lesion failure (TLF) composite endpoint [cardiac death, MI not clearly attributable to a non‐target vessel, and clinically driven target lesion revascularization (TLR)] at 1‐year. Results: Baseline patient demographic, angiographic, and stenting characteristics were similar in both study arms. A single stent technique with provisional or "cross over" stenting were the most widely used in both arms (93.2% BP‐SES vs. 92.4% PP‐EES). Freedom from TLF at 1‐year was 94.7% for BP‐SES and 91.9% for PP‐EES ( P for noninferiority 0.031). The rate of clinically driven target lesion revascularization (TLR) at 1‐year was 3.2% for BP‐SES and 3.0% for PP‐EES ( P  = 0.95). There were no significant differences detected in any of the individual clinical endpoints or other secondary clinical endpoints between the study arms at 1‐year follow up. Conclusions: The new bioresorbable polymer sirolimus‐eluting stent showed safety and efficacy profiles similar to durable polymer everolimus‐eluting in the treatment of patients with bifurcation lesions at 1‐year follow up. © 2015 Wiley Periodicals, Inc.